2016
DOI: 10.1002/cpdd.240
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Study of Safety, Tolerability, and Pharmacokinetics of PTC299, an Inhibitor of Stress‐Regulated Protein Translation

Abstract: PTC299 is a novel small molecule that specifically blocks the production of protein from selected mRNAs that under certain conditions use noncanonical ribosomal translational pathways. Hypoxia, oncogenic transformation, and viral infections limit normal translation and turn on these noncanonical translation pathways that are sensitive to PTC299. Vascular endothelial cell growth factor (VEGF) is an example of a transcript that is posttranscriptionally regulated. Single doses of PTC299 (0.03 to 3 mg/kg) were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
(31 reference statements)
3
13
0
Order By: Relevance
“…Comprehensive preclinical IND-enabling safety pharmacology, toxicology and genotoxicity studies (Supplementary Materials and Methods in the Supplementary Data file) demonstrated that PTC299 is safe and well tolerated in pre-clinical studies (Supplementary Table S5). Subsequently, several clinical trials in healthy volunteers and in patients with solid tumors were conducted to assess PTC299(28, 29), including a prospective Phase 2a study in 2009–2010 in patients with neurofibromatosis type 2, an autosomal dominant tumor suppressor syndrome characterized by bilateral vestibular Schwannomas. Eleven patients were enrolled including 4 males and 7 females with a median age of 25 (range 19–44) at the time of enrollment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive preclinical IND-enabling safety pharmacology, toxicology and genotoxicity studies (Supplementary Materials and Methods in the Supplementary Data file) demonstrated that PTC299 is safe and well tolerated in pre-clinical studies (Supplementary Table S5). Subsequently, several clinical trials in healthy volunteers and in patients with solid tumors were conducted to assess PTC299(28, 29), including a prospective Phase 2a study in 2009–2010 in patients with neurofibromatosis type 2, an autosomal dominant tumor suppressor syndrome characterized by bilateral vestibular Schwannomas. Eleven patients were enrolled including 4 males and 7 females with a median age of 25 (range 19–44) at the time of enrollment.…”
Section: Resultsmentioning
confidence: 99%
“…PTC299 was identified as an inhibitor of the translation of VEGFA mRNA using PTC Therapeutics’ proprietary GEMS™ technology phenotypic screening platform(27). PTC299 was in clinical trials for the treatment of solid tumors (28, 29) and is currently being reevaluated for use in hematologic cancers. To guide safe and effective precision cancer treatment, we performed extensive biochemical characterization of PTC299 and demonstrated that it interacts with and inhibits dihydroorotate dehydrogenase (DHODH), a rate limiting enzyme in the de novo biosynthesis of pyrimidine nucleotides(5).…”
Section: Introductionmentioning
confidence: 99%
“…PTC-510 inhibited tumor growth in a mouse xenograft model at an oral dose as low as 10 mg/kg, bid . Through further lead optimization and preclinical studies, we selected a Drug Candidate, PTC299 that is more potent than PTC-510 in controlling tumor growth in vivo and is currently under further preclinical and clinical evaluation [42;43]. The data on in vitro and in vivo characterization of PTC299 will be published separately as this is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…This can result in severe or life threatening side effects such as bleeding, arterial and venous thrombosis, hypertension, asymptomatic proteinuria and nasal septal perforation in some individuals [44]. Moreover, growing evidence suggests that blockage of global VEGF signaling stimulates the body to respond by initiating by-pass processes that can then be co-opted by the tumor, leading to evasive resistance [42;45;46]. One of the underlying mechanisms of this evasive resistance range from greater production of VEGF itself to elevation of other pro-angiogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…PTC299 was originally identified as a compound that modulates expression of stressregulated proteins like VEGF and was only subsequently found to be a DHODH inhibitor (Cao et al, 2019;Weetall et al, 2016). DHODH inhibitors have been shown to suppress virallyinduced inflammatory cytokine production (Xiong et al, 2020).…”
Section: Ptc299 Inhibits Production Of Inflammatory Cytokinesmentioning
confidence: 99%